2009
DOI: 10.28945/63
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teachers Perceptions of Web-Based Learning Tools

Abstract: Over the past 8 to 10 years, web-based learning tools (WBLT s), also known as learning objects, have been evaluated and received positively by higher education students. However, little research has been done examining teachers perceptions of these tools, particularly in middle and secondary school environments. The purpose of the current study was to analyse teacher perceptions of the use of WBLT in middle and secondary school classrooms. Data collected from the Learning Object Scale for Teachers (LOES-T) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 33 publications
(84 reference statements)
1
47
0
3
Order By: Relevance
“…It proves that students are satisfied and interested with teaching and learning using web-based resources. This finding is similar to the results obtained by (Kay, Knaack, & Petrarca, 2009) who found that the students' performances increased significantly (almost by 40%) when they use web resources.…”
Section: Figure 2 3d Space Interactive Appletsupporting
confidence: 82%
“…It proves that students are satisfied and interested with teaching and learning using web-based resources. This finding is similar to the results obtained by (Kay, Knaack, & Petrarca, 2009) who found that the students' performances increased significantly (almost by 40%) when they use web resources.…”
Section: Figure 2 3d Space Interactive Appletsupporting
confidence: 82%
“…A closer look at the research literature shows that the concept of WBLR is similar to the term "Web-based learning tools", also referred to as "learning objects", found in Knaak, (2005, 2008) and Kay, Knaak, and Petrarca (2009). The term is defined as "interactive Webbased tools that support learning by enhancing, amplifying, and guiding the cognitive processes of learners."…”
Section: The Concept Of Wblrmentioning
confidence: 99%
“…A few participants indicated prior knowledge of teaching best practices, but overall, participants cited the e-learning experiences as complementary best practice for beginning teacher educators. The improved planning and implementation skills reflect the findings of Alger andKopcha (2009), Downey (2008), Kay, Knaack, andPetrarca (2009), Shepherd andHannafin (2008), Snoeyink (2010), andYeh (2007). Participants reported improved lesson planning, improved lesson implementation, visual interpretations of best practices, modeling, and peer and university instructor feedback as successes of the e-learning project.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 66%